Dose Response Satu Biotip Eleusine Indica Resisten-Parakuat Terhadap Parakuat, Glifosat, dan Ammonium Glufosinat - Titania Ade Yulivi; Edison Purba; Nini Rahmawati (Universitas Sumatera Utara, 2014)
Goosegrass (Eleusine indica) is one of weeds that had negative effect which is commonly found incorn field. In the past few years the existence of this weed in the area of BBI Tanjung Selamat hasbeen reported that population was difficult to control with paraquat. This research aims to determinethe dose response of the suspicioned resistant population to paraquat, glyphosate, and ammoniumglufosinate. The levels of paraquat applied were 0, 50, 100, 200, 400, 800, 1600 g a.i. ha-1;glyphosate at 0, 60, 120, 240, 480, 960,1920 g a.i. ha-1 and ammonium glufosinate at 0, 55, 110,220, 440, 880, 1760 g a.i. ha-1. The treatments were arranged in randomised block design (RBD)and each treatment was made in three repetition. The results showed that the paraquat-resistantpopulation from area of BBI still survived as much of 11,67% at the rate of 400 g a.i ha-1.Meanwhile, glyphosate and ammonium glufosinate controlled satisfactorily this population.Keywords: Paraquat, Glyphosate, Ammonium Glufosinate, Eleusine indica, Resistance